Design, Fabrication and Experimental Validation of a Piezoelectric Energy Harvester for Smart Vehicles - Basharat, Zaryab; Buzal, Muhammad Zaid; Malik, Muhammad Haris; Saleem, Wania (Journal of Electronics and Electrical Engineering, 2026)
Piezoelectricity has become the focus of researchers because of the ability of piezoelectric materials to convert applied mechanical stress into electricity. There has been a great interest in harvesting energy from vibrations generated by car engine in running condition. Suitable energy harvester can be used to convert these vibrations into electricity. In this research, we have designed a piezoelectric cantilever beam type configuration for energy harvesting from engine's vibrations. Number of calculations are made and the disk shape of PZT-5A having 36 mm diameter is selected. Every disc of PZT-5A has a diameter of 36 mm, meaning it has an active area of nearly 9.62 cm2, making up an aggregate area of 67.3 cm2 for seven discs, a damping factor of 0.03 was assumed. The harvested energy is then temporarily stored in the capacitor bank. The battery control unit is designed using Raspberry Pi microcontroller, which controls the battery supply. When battery is charged to certain limit then, it will stop charging the battery and supply is directly applied to load, and when battery is below certain limit, then it will charge the battery first. Both analytical and simulation-based results are obtained and there has been a close match. A cantilever beam with piezoelectric attached is designed and fabricated using the simulation and analytical results. The system is then mounted on engine' head and experiments were performed for 500, 750, 1,000, 1,250, and 1,500 rpms and output voltages were noted as 14.51, 9.47, 7.14, 6.69 and 5.17 volts respectively. It was concluded that there has been a close match with analytical results. Experimental validation with the engine mounted in the running vehicle has proved the concept's validity with regards to the use of waste engine vibrations for the generation of sustainable energy.